Editorial: Wireless sensor networks based on environmental energy harvesting - Han, Guangjie; Shu, Lei; Pathan, Al-Sakib Khan; Rodrigues, Joel J. P. C.; Mellouk, Abdelhamid (Hindawi Publishing Corporation, 2013)
With the development of wireless sensor networks (WSNs), more complicated and challenging applications now can be targeted by small and smart systems. Although most of these applications require little power, the gradual degradation of the batteries further decreases the useable lifetime of WSNs. Aside from relying on revolutionary development of battery technologies, one of the most important ways to improve the system lifetime is to “harvest” energy from ambient environmental energy sources. Energy harvesting devices efficiently and effectively capture, accumulate, store, condition, and manage this energy and supply it in a form that can be used to perform a helpful task.